2022
DOI: 10.1111/ijfs.15577
|View full text |Cite
|
Sign up to set email alerts
|

Wasted bread flour as a novel ingredient in cake making

Abstract: Bread is one of the most wasted products in both industry and retail. This study analysed the use of bread flour of various particle sizes (1000 lm, 500 lm and 200 lm) in different percentages for sponge formulations (10% and 20%) and layer cakes (10%, 20% and 30%). Viscosity, microstructure and density of batters, as well as specific volume, texture and colour of cakes were evaluated. The inclusion of bread flour change batter microstructure. Viscosity does not affect the sponge batters but it tends to increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The results of this study are similar to those obtained by Cardoso et al ( 2019) on wheat and rye flours, but in this research, mold and yeast counts are somewhat lower. These would suggest that the flours from these types of bread could be used for human food, such as the production of cookies (Guerra-Oliveira et al, 2021) or cakes (Guerra-Oliveira et al, 2022), and thus reduce food waste. Alpers et al (2021) argue that the absence of visual detection is sufficient to eliminate the risk of mycotoxin growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study are similar to those obtained by Cardoso et al ( 2019) on wheat and rye flours, but in this research, mold and yeast counts are somewhat lower. These would suggest that the flours from these types of bread could be used for human food, such as the production of cookies (Guerra-Oliveira et al, 2021) or cakes (Guerra-Oliveira et al, 2022), and thus reduce food waste. Alpers et al (2021) argue that the absence of visual detection is sufficient to eliminate the risk of mycotoxin growth.…”
Section: Resultsmentioning
confidence: 99%
“…In households, stale bread is often ground and used in several culinary recipes. Considering that bread is wasted throughout the food supply chain, the industry sector has come up with several options for its reuse, such as the preparation of sourdoughs (Gélinas, McKinnon, & Pelletier, 1999), cookies (Guerra-Oliveira, Belorio, & Gómez, 2021), cakes (Guerra-Oliveira, Belorio, & Gómez, 2022), snacks (Samray, Masatcioglu, & Koksel, 2019), and beer (Brancoli, Bolton, & Eriksson, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Still remaining in the field of cereal-based products, the use of bread’ leftovers that are withdrawn from the market due to texture issues, but that has not experienced microbial deterioration, is being considered. In this regard, research has shown that these materials could be incorporated to produce bread, cakes, or cookies ( 26 ). However, these additions can have negative implications on the quality of final products, especially on their organoleptic acceptability, which makes necessary focused research to minimize these negative problems, mainly by optimizing the percentages that can be incorporated to achieve final products with acceptable organoleptic properties.…”
Section: The Consumer’s Choice For “Clean Label” Foods and New Natura...mentioning
confidence: 99%
“…There is a growing need to reformulate bakery products to increase their nutritional value while maintaining their sensory appeal in response to the rising interest in healthier dietary options. The investigation of novel ingredients that can not only replace conventional ingredients but also improve the overall quality and healthfulness of bakery goods has been sparked by this paradigm shift (Salehi, 2020;Guerra-Oliveira et al, 2022). In this culinary transformation, foxnut emerges as a viable choice due to its distinctive combination of macronutrients, micronutrients and bioactive substances (Kumar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%